A Longitudinal Study on the Relationship of Oral Health at 4 Years of Age with That in Adulthood - Sho Yamada; Reiko Sakashita; Mikinori Ogura; Eiko Nakanishi; Takuichi Sato (MDPI AG, 2021)
This longitudinal study aimed to clarify the relationship of oral health in infancy with that in adulthood among participants who were the subjects of the oral health promotion project (OHPP) conducted in Miyako Island, Okinawa Prefecture, Japan, since 1984. Twenty-seven subjects, around 35 years of age, were examined for dental caries, periodontal diseases (community periodontal index), dental plaque, occlusion, and bite-force and compared with those at 4 and 13-15 years of age. The dental caries status and maximum bite force in adulthood was significantly reflected for those at 4 and 13-15 years of age (p < 0.05). CPI in adulthood was related to the dental caries status at 4 and 13-15 years of age but not to the gingival score at 4 years of age, and it was weakly related to the gingival score at 13-15 years (r = 0.264, p > 0.05). Most of the normal occlusion at 4 years of age became normal permanent occlusion in adulthood (88.9%). Most of the cases involving the discrepancy factor retained the same condition in both the deciduous and permanent dentitions (83.3%) (p < 0.001). Those who participated in the OHPP soon after birth showed significantly fewer DMFT (p < 0.05) compared with those who did not. This study revealed that oral health at 4 years of age was related to that in adulthood, suggesting that fostering good oral health soon after birth is of great importance.